Security and Privacy Cloud Storage as a Personal Digital Archive Storage Media - Kusumawardhani, Dwininda; Masyithah, Deby Claudia (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
Background of the study: The increasing use of Internet technology has given rise to new challenges in the protection of privacy and personal data, especially with the increasing practice of collecting, using and distributing one's personal data. Lagging instruments and regulations is one of the triggers for the weak mechanism of protection against privacy and personal data, especially in the use of cloud storage technology.Purpose: This article aims to find out the security of managing archive storage in a cloud.Method: The method used in this paper is a literature review.Findings: The result indicates that cloud storage has created new legal problems, namely how personal data from cloud storage users are protected from various kinds of disclosure and distribution by cloud storage service providers to third parties, while in Indonesia itself the ITE (Information and Electronic Transactions) Law has not clearly regulated security protection from private files stored in the cloud storage.Conclusion: This is an obstacle to cloud storage to be able to continue to grow like the Internet which has become a prima donna in human life.